A pilot multicenter randomized controlled trial on individualized blood pressure targets versus standard care among critically ill patients with shock - Rakshit Panwar; Bairbre McNicholas; Ciprian Nita; Alison Gibberd; Amber-Louise Poulter; Marcia Tauares; Lauren Ferguson (Journal of Intensive Care)
Abstract Background Minimizing relative hypotension, or mean arterial pressure (MAP) deficit, by targeting patients’ own pre-illness MAP (individualized MAP) during vasopressor therapy is a potential strategy to improve outcomes among ICU patients with shock. We conducted a prospective, open label, parallel-group, pilot RCT to assess feasibility and safety of this intervention compared to standard care. Methods Thirty-seven eligible patients, aged 40 years or older and receiving vasopressor support for shock, were randomly allocated to individualized MAP target (N = 17) or standard MAP target (N = 20) at two multidisciplinary ICUs in Australia and Ireland. Pre-specified endpoints were time-weighted average MAP-deficit (i.e., percentage difference between patients’ pre-illness MAP and achieved-MAP), percentage time spent with > 20% MAP-deficit, major adverse kidney events (MAKE-14), 14-day and 90-day all-cause mortality, and cardiovascular adverse events within 28 days of randomization. All comparisons of efficacy outcomes were exploratory. Results The median MAP-deficit and percentage time with > 20% MAP-deficit with individualized MAP vs. standard MAP were 7% [interquartile range: 2–16] vs. 18% [9–23] (p = 0.048), and 8% [0–43] vs. 53% [14–75] (p = 0.03), respectively. MAKE-14 (2/17 (12%) vs. 4/20 (20%), p = 0.67), 14-day mortality (1/17 (6%) vs. 3/20 (15%), p = 0.61), 90-day mortality (2/17 (12%) vs. 4/20 (20%), p = 0.67) and cardiovascular adverse events were similar for both groups. Conclusions This pilot RCT demonstrated that an individualized MAP target strategy was feasible to implement. No adverse safety signals were evident. These data and study procedures helped inform the design of a definitive RCT on the question of individualized MAP targets among critically ill patients with shock. Study registration: ACTRN12618000571279.